2020
DOI: 10.1186/s12955-020-01516-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of occupational, demographic and health determinants in Canadian reservists veterans and the relationship with poor self-rated health

Abstract: Background: Self-rated health is an useful indicator of the general health in specific populations and used to propose interventions after service in the military context. However, there is scarce literature about self-rated health (SRH) in the Canadian Veterans of the Reserve Force and its relationship with demographic, health and occupational characteristics of this specific group. The aims of this research were to determine the SRH in Canadian Reserve Force Veterans and to explore the relationship between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Of those articles that did include race, ethnicity, or ethno-cultural identity, these important components of social identity were treated solely as demographic variables, without implementing GBA+ in the analysis. [10][11][12][13][14] Fourteen of the articles were based on data collected in projects with data collection ending in 2016, [10][11][12][15][16][17][18][19][20][21][22][23][24][25] and seven did not clearly indicate when their data were collected, [26][27][28][29][30][31][32] raising the question of whether GBA+ was considered when the projects were initially conceived and data collection occurred.…”
Section: Resultsmentioning
confidence: 99%
“…Of those articles that did include race, ethnicity, or ethno-cultural identity, these important components of social identity were treated solely as demographic variables, without implementing GBA+ in the analysis. [10][11][12][13][14] Fourteen of the articles were based on data collected in projects with data collection ending in 2016, [10][11][12][15][16][17][18][19][20][21][22][23][24][25] and seven did not clearly indicate when their data were collected, [26][27][28][29][30][31][32] raising the question of whether GBA+ was considered when the projects were initially conceived and data collection occurred.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple aspects impact quality of life: biological, sociocultural, and demographical, among others. Mental health issues in the military population range between 9% and 26% [25][26][27] . Oznur et al 25 analyzed 258 SF-36 questionnaires completed by Turkish military members who participated in armed conflicts in Afghanistan, and found the lowest scores in the areas of mental health (59.14 ± 18.56) and vitality (59.25 ± 21.17).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased psychological distress due to the pandemic was accompanied by a significant decrease in resilience and more serious anxiety and depression symptoms. It has been found that self‐rated health, as an indicator, is associated with objective health status, healthy behaviors, and functioning, and can be a simple predictor of anxiety and depressive symptoms (Reyes et al, 2020 ). Resilient individuals are more capable of dealing with fears arising from SARS‐CoV‐2‐related stressors; they also tend to experience positive emotions and thoughts, and seek the necessary social support from others, and vice versa (Ye et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%